Diffusion Tensor Imaging in First Degree Relatives of Schizophrenia and Bipolar Disorder Patients - Arat, Hidayet E. (Schizophr Res, 2014)
OBJECTIVES: White matter (WM) abnormalities are one of the most widely and consistently reported findings in schizophrenia (SZ) and bipolar disorder (BD). If these abnormalities are inherited determinants of illness, suitable to be classified as an endophenotype, relatives of patients must also have them at higher rate compared to the general population. In this review, we evaluate published diffusion tensor imaging (DTI) studies comparing first degree relatives of SZ and BD patients and healthy control subjects. METHODS: We searched PubMed, Embase and PsychInfo for DTI studies which included an unaffected relative and a healthy comparison group. RESULTS: 22 studies fulfilled the inclusion criteria. WM abnormalities were found in many diverse regions in relatives of SZ patients. Although the findings were not completely consistent across studies, the most implicated areas were frontal and temporal WM regions and the corpus callosum. Studies in relatives of BD patients were fewer in number with less consistent findings reported across studies. CONCLUSIONS: Our review supports the concept of WM abnormalities as an endophenotype in SZ, with somewhat weaker evidence in BD, but larger and higher quality studies are needed to make a definitive comment.